PEMBUATAN DEKSTRIN DARI PATI UBI KAYU MENGGUNAKAN ENZIM AMILASE DARI AZOSPIRILLUM sp. JG3 DAN KARAKTERISASINYA - Dian Riana Ningsih; Ari Asnani; Amin Fatoni (Universitas Jenderal Soedirman, 2010)
Amylase enzyme is used to hydrolyze starch into simpler molecules such as dextrin. Amylase can be isolated fromAzospirillum sp. JG3 bacteria. The purpose of this study was to characterize dextrins from cassava starch (Manihot esculenta) is catalyzed by the enzyme amylase from Azospirillum sp. JG3 bacteria. Stages of this study are: determination of optimum substrat and to analyze the chemical and physical dextrins including moisture content, ash content, dexstrosa equivalent (DE) and the yield obtained. The result of this research showed that optimum condition hydrolysis starch of cassava that using amylase from Azospirillium sp. JG3 bacteria was acquired at substrate concentration 3% and the results of analysis obtained dextrins include yield of 96.67%, water content of 9.39%, 0.25% ash content and dexstrosa equivalent (DE) of 16.55.